2016
DOI: 10.1016/j.jss.2016.01.004
|View full text |Cite
|
Sign up to set email alerts
|

The daily stand-up meeting: A grounded theory study

Abstract: Context: The daily stand-up meeting is one of the most used agile practices but has rarely been the subject of empirical research. Aim: The present study aims to identify how daily stand-up meetings are conducted and what the attitudes towards them are. Method: A grounded theory study of the daily stand-up meeting was conducted with twelve software teams in three companies in Malaysia, Norway, Poland and the United Kingdom. We interviewed 60 people, observed 79 daily stand-up meetings and collected supplementa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
81
0
13

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 100 publications
(98 citation statements)
references
References 65 publications
4
81
0
13
Order By: Relevance
“…Further, because meeting satisfaction is part of overall job satisfaction [13], it is important to understand what makes this meeting valuable for team members. In a recent, qualitative study of thirteen teams (in Norway, Poland, UK and Malaysia) we found that the attitudes towards DSMs were slightly more positive than negative [5]. However, the level of satisfaction varied within the teams.…”
Section: Introductionmentioning
confidence: 85%
See 4 more Smart Citations
“…Further, because meeting satisfaction is part of overall job satisfaction [13], it is important to understand what makes this meeting valuable for team members. In a recent, qualitative study of thirteen teams (in Norway, Poland, UK and Malaysia) we found that the attitudes towards DSMs were slightly more positive than negative [5]. However, the level of satisfaction varied within the teams.…”
Section: Introductionmentioning
confidence: 85%
“…The personal gain from the meeting is thus reduced. Moreover, being able to have quick problem-solving discussions in the DSM make developers perceive the DSM as more valuable [5]. Senior developers often work on more complex tasks, and it might be that high complexity problems are seldom discussed at the meeting because they require too much time.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations